Prevalence of chlamydia trachomatis infections and associated risk factors in different populations of both gender in Manaus City - Benzaken, Adele S.; Galban, Enrique; Moherdaui, Fábio; Pedroza, Valderiza; Naveca, Felipe G.; Sardinha, José Carlos G.; Araújo, Adauto (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: infection by Chlamydia trachomatis (CT) is an STD of high prevalence in the world and when it is not diagnosed it can, especially among women, progress with grave sequels. In Brazil, the epidemiological behavior trend of the infection is not well-known. Objective: estimate the prevalence and factors associated with the infection by Chlamydia trachomatis in segments of the sexual active population of Manaus. Methods: during 2004 and 2005 a study was performed of seccional cuts with 1.762 people (1.007 women and 755 men) divided in groups of low risk (598 preg nant women and 600 manufacture industry workers) and of higher vulnerability (409 women and 155 men in STD clinics). For the diagnostic, hybrid capture/DIGENE in women and PCR “Cobas Amplicor CT/NG/Roche” in men. Results: the global prevalence was of 7.5% in women and 11.1% in men, with 2.8% (p = 0). The prevalence for pregnant women with STD were 11.9% and 10% (p = 0.36) and 3% and 1.9% for manufacture industry workers and men with STD (p = 0.65). High prevalence was observed in adolescents and pregnant women (14.8%). Women showed a risk of infection four times higher than those of men, [ORprev. = 4,38 (C.I. 95% 2.66-7.26); p = 0]. The prevalence reason was 4 and the prevalence attributed to women was 8.3. The prevalence in women with more than one sexual partner was of 16.6% (42/253), superior to those that had only one partner, who had a prevalence 9.3% (70/753 p = 0.001). This is two times the risk of infection [ORprev. = 1,74 (OR 95% 1.26-2.99); p = 0,002]. Women with part ners that had urethral discharge worsened the prevalence rate [OR = 4.4 (IC 95% 2.15-9.21); p = 0.0000104]. The co-infection with Neisseria gonor rhoea happened in 17.3% of the cases. Conclusion: the prevalence of women is intermediary (approximately 10%) when compared to those rates published in international literature. The prevalence in women is significantly higher than those of men and higher prevalence corresponds to adoles cents. The main factors associated with the infection were the increment in the number of partners and having partners with urethral discharge.